EVALUASI SISTEM INFORMASI ELECTRONIC DAILY PERFORM REPORT (E-DPR) DENGAN MENGGUNAKAN FRAMEWORK COBIT 5 - Afif Khoirul Abdi; Endro Kuswoyo; Indah Purnamasari (Jurnal informasi dan komputer, 2022)
XYZ College is one of the private universities in East Jakarta that has used Information Systems (SI) into its business processes, one of which is the Electronic Daily Performance Report (E-DPR) to record employee activities and performance appraisals or Key Performance Index. . However, in practice the system has never been monitored and evaluated regularly since it was implemented and socialized to employees until now. So that the achievement of goals and obstacles is not yet known by the agency. Based on this, it is necessary to evaluate the Electronic Daily Performance Report (E-DPR). This evaluation uses the capability model as a measuring tool for respondents answers, the questionnaire is made using a Likert scale measurement based on statement points / audit questions in the COBIT 5 framework in the MEA domain (Monitor, Evalute and Assess) as a guide. Based on the results of the recapitulation of respondents answers, the capability level value in the MEA01 domain is 3.88, the MEA02 domain is 3.58 and the MEA03 domain is 3.50 in the range 0-5. In order for agencies to obtain the desired results, an analysis of the performance of the E-DPR system is carried out and provides recommendations for agencies to improve the performance of the E-DPR system at the XYZ College, Jakarta.